The Desert Crop - Cookson, Catherine (London Bantam Press, 1997)
Money was tight in the farming communities around Fellburn in the 1880s, so when Hector Stewart announced to his children that he was to marry Moira, a wealthy distant relative, it was Daniel the youngest who guessed the purpose of the union
Keywords: Farm life -- Manners and customs -- England